Trialling a volunteer workforce to provide psychosocial care to hospital inpatients: a plan-do-study-act project. Issue 4 (2nd April 2022) - McKeown, Debi; Byrnes, Kate
Abstract : Introducing a novel volunteer workforce to assist patients in hospital who require 1:1 support has potential benefits, such as reducing expenditure on additional clinical staff and ensuring that patients receive holistic care. This study aimed to determine whether a volunteer workforce could effectively provide psychosocial support to hospital patients and relieve pressure on staff. A plan-do-study-act approach was used to introduce a team of volunteers to an NHS hospital and assess the impact. The volunteers were trained to provide psychosocial support to patients requiring level two and above enhanced observations across 19 acute medicine wards. A new approval system was also introduced to review requests for bank staff. A 14-week audit was conducted to assess the impact of the intervention on expenditure and required patient observation levels. The results showed that introducing a voluntary workforce led to savings of £705 000 in 1 year from reduced reliance on bank staff. The number of patients requiring level three observation and the frequency of falls also declined. This study indicates that implementing a volunteer workforce is an effective and feasible approach to providing psychosocial care to patients, relieving pressure on the NHS workforce and reducing expenditure on bank staff.